KAJIAN TAFSIR TEMATIK: AL-QUR’AN DAN PENYEBUTAN MANUSIA - Abdul Hadi (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
Humans are said to be the pinnacle of Allah SWT's creation who occupy the highest position in the discussion of the Qur'an, so that many verses of the Qur'an inform knowledge about humans, both their nature, character, position, responsibilities up to the stages of their creation. The term human in the redaction of the verses of the Qur'an has several terms such as al-insân, al-nâs, basyar, anâsiyya, insiyya and banî âdam. From these terms and several other supporting data, the meanings will be revealed so that the meaning of the appropriate terminology for referring to Allah SWT's creature called 'human' is wide open.